Characterization of Fructan Metabolism During Jerusalem Artichoke (Helianthus tuberosus L.) Germination - Jiao, Jiao; Wang, Ji; Zhou, Mengjia; Ren, Xuyang; Zhan, Wenyue; Sun, Zongjiu; Zhao, Haiyan; Yang, Yao; Liang, Mingxiang; Ende, Wim Van den (Frontiers in Plant Science, 2018)
The inulin-type fructans in Jerusalem artichoke (Helianthus tuberosus L.) tubers exhibit different degrees of polymerization and are critical for germination. We aimed to characterize the sugar metabolism dynamics in the tubers without bud eyes or shoots (T) and bud eyes plus shoots (BE/S) of indoor- and field-grown Jerusalem artichokes during germination. Ht1-FEH II and Ht1-FEH III (1-fructan exohydrolases II and III, inulin-degrading enzymes) expression increased 5 days after planting indoors, whereas Ht1-FEH II expression increased 72 days after planting in the field in T and BE/S. Ht1-SST (sucrose:sucrose 1-fructosyl transferase, inulin synthesis initiator) and Ht1-FFT (fructan:fructan 1-fructosyl transferase, inulin elongator) expression generally decreased in indoor-grown T. The enzyme activities of 1-FEH and 1-FFT were unchanged during germination in both indoor- and field-grown T and BE/S, whereas 1-SST activity decreased in indoor-grown T, while 1-FEH and 1-FFT activities increased as a function of germination time in BE/S of both indoor- and field-grown tubers. The total soluble sugar content gradually decreased in T after germination indoors or in the field, while at the end of germination, the sucrose and fructan contents decreased and fructose content increased in the field. The enzyme activities of soluble vacuolar (VI) or neutral invertase (NI) did not change significantly, except at the late germination stage. Sucrose synthase (SS) and sucrose-phosphate synthase (SPS) activities were not significantly changed in T and BE/S in indoor-grown artichokes, while SS activity gradually increased and SPS activity gradually decreased in field-grown artichokes, alongside sucrose degradation. Compared to T, BE/S generally had higher enzyme activities of 1-FEH and 1-FFT, promoting inulin hydrolysis. This work shows that the process of tuber germination is similar indoors and in the field, and germination studies can therefore be conducted in either environment.